Molecular docking investigation of calotropone as a potential natural therapeutic agent against pancreatic cancer - Agnia Purnama; Diva Rayyan Rizki; Intan Qanita; Muhammad Iqhrammullah; Khairunnas Ahmad; Vivi Mardina; Kana Puspita; Kartini Hasballah (Wolters Kluwer Medknow Publications, 2022)
A natural bioactive compound named calotropone has been reported as a drug candidate for several cancers, including pancreatic cancers. Herein, we used molecular docking approach to test the possible mechanisms of action of calotropone in inhibiting the growth of pancreatic cell cancer with gemcitabine as the positive control. By employing AutoDock Vina, we studied the molecular interaction between calotropone and pancreatic cancer-associated proteins, namely Glucosaminyl (N-Acetyl) Transferase 3, Glutamic-Oxaloacetic Transaminase 1, Tyrosine-protein kinase Met (c-Met), peroxisome proliferator-activated receptor γ, Budding Uninhibited by Benzimidazole 1, A Disintegrin and Metalloproteinase 10, Sex-determining region Y and Nuclear Factor kappa Beta (Nf-Kβ). Higher affinity energies of calotropone toward the aforementioned proteins (ranging from ‒7.3 to ‒9.3 kcal/mol) indicate that calotropone may work in the same manner as anticancer drug gemcitabine. Highest docking score was found at the interaction of calotropone and Nf-Kβ (‒9.3 kcal/mol).